Setting up your Go development docker environment - Rice, Liz (O'Reilly Media, Inc., 2018)
Are you a Go programmer looking to introduce Docker containers into your workflow? In this lesson, you'll learn how to set up a containerized development environment that rebuilds Go code automatically as you edit it. You'll learn how to use tools such as Realize, and how to generate a small and efficient container image for production distribution using Docker Multistage Builds.